The young scientist book of evolution - Cork, Barbara; Bresler, Lynn. (London ; Tulsa, Okla. : Usborne : EDC [distributor], 1985)
Explains how scientific discoveries in genetics, animal behavior, and the study of fossils have changed our ideas about the origin and development of life on earth.
Spine title: Evolution.
6.9
5-8
Keywords: Evolution (Biology) -- Juvenile literature; Evolution; Evolution